Analysis of the Ability to Understand the Basic Law of Chemistry for Science High School Students - Irma Ragentu; Suherman Suherman (Universitas Tadulako, 2022)
This study aimed to describe the student's capability of grade XI Science at SMA 3 Palu in understanding Fundamental Chemical Laws. This study was a qualitative descriptive study. The sample was students in the class XI Science 7, which amounted to 29 students, and XI Science 8, which amounted to 31 students. The sample was determined based on nonprobability sampling with a purposive technique based on the suggestions from the chemistry teacher that the two classes were homogeneous. Data were obtained from the test of students' understanding of fundamental Chemical Laws consisting of six essay questions and supported by the interview results. Respondents for the interview were six students based on the categorization of high, medium, and low scores, which were obtained from the calculation of the average score of students and standard deviation. The results showed that the capability on understanding Fundamental Chemical Laws of students of grade XI Science at SMA 3 Palu which was included in the high category was the ability to interpret as much as 79.58%, and included in the sufficient category was the ability to classify as much as 56.25%, while those included in the low category was the ability to exemplify, conclude, compare, and explain, with successive as much as 30, 24.58, 32.08, and 40.42%, respectively.